Synthetic Biology Innovations in Designing Cellulose-Based Smart Drug Delivery Systems - Samy Selim; Mohammed S. Almuhayawi; Soad K. Al Jaouni; Mohammad Harun-Ur-Rashid (BioResources)
The integration of synthetic biology with cellulose-based materials has paved the way for groundbreaking advancements in smart drug release and delivery systems. Synthetic biology, through precise genetic engineering and the creation of programmable biological circuits, enables the development of drug carriers that can respond dynamically to specific physiological cues, such as pH changes. For example, the contrast in pH between the stomach (pH ~1.5 to 3.5) and the intestines (pH ~6 to 7.5) has been exploited in cellulose-based systems to achieve site-specific drug release. Cellulose offers an ideal platform for constructing these responsive drug delivery systems. This review explores recent innovations in genetically engineered cellulose, functionalization strategies via synthetic biology, and advanced biofabrication techniques such as 3D bioprinting and microfluidics. Applications of these systems span cancer therapeutics, antimicrobial treatments, chronic disease management, and emerging areas like personalized medicine and gene therapy. Challenges related to biocompatibility, scalability, and regulatory approval persist. Future directions involving CRISPR-Cas9-mediated cellulose modification, machine learning for optimized drug release, and sustainable production strategies highlight the transformative potential of these systems in precision medicine. This review provides comprehensive insights into the current state and future prospects of cellulose-based smart drug delivery, offering a roadmap for advancing next-generation therapeutics.